The Use of Kahoot Application as a Learning Media to Improve Students' Vocabulary Mastery in Seventh Grade SMP Negeri 1 Ciomas - maesaroh, Maesaroh; Juniardi, Yudi; Rahmawati, Dina (Globish: An English-Indonesian Journal for English, Education, and Culture, 2025)
The use of technology in education has become an integral component. This study aimed to investigate the effectiveness of the Kahoot application as a learning medium for seventh-grade students at SMPN 1 Ciomas in the academic year 2023/2024. The study employed a qualitative-quantitative approach through Collaborative-Classroom Action Research conducted in two cycles. The research sample consisted of 27 students from class VII E. Data were collected through participatory observation, pre-tests, post-tests, and closed questionnaires. Data analysis results indicated pre-test and post-test values at a significance level of 5% with degrees of freedom of 26 and a t-table value of 2.056, where the t-value for Cycle I was higher than the t-table (6.421 > 2.056) and for Cycle II was also higher than the t-table (9.593 > 2.056). Observations showed a significant increase in student participation levels, shifting from "Fair" in Cycle I to "Very Good" in Cycle II. Questionnaire responses were highly positive, with an average score of 82.24%, indicating student satisfaction and engagement with the Kahoot application. Overall, this study concludes that the Kahoot application could be used as an alternative learning medium or tool to enhance students' vocabulary at SMPN 1 Ciomas.Keywords: Kahoot Application, Vocabulary Mastery, Action Research